2020
DOI: 10.3390/ijms21197004
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Role of Microbial Surfactants, with Special Emphasis on Fish

Abstract: Microbial surfactants (biosurfactants) are a broad category of surface-active biomolecules with multifunctional properties. They self-assemble in aqueous solutions and are adsorbed on various interfaces, causing a decrease in surface tension, as well as interfacial tension, solubilization of hydrophobic compounds, and low critical micellization concentrations. Microbial biosurfactants have been investigated and applied in several fields, including bioremediation, biodegradation, food industry, and cosmetics. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 97 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…To date, trehalolipids have been poorly investigated as natural compounds for pharmaceutical applications [59]. Herein, we have demonstrated that the enriched fraction of succinoyl trehalolipids exerted high antiproliferative activity on a prostate cancer cell line (PC3) at 100 µg/mL while being significantly less cytotoxic to the normal counterpart (PNT2) (Figure 3).…”
Section: Discussionmentioning
confidence: 87%
“…To date, trehalolipids have been poorly investigated as natural compounds for pharmaceutical applications [59]. Herein, we have demonstrated that the enriched fraction of succinoyl trehalolipids exerted high antiproliferative activity on a prostate cancer cell line (PC3) at 100 µg/mL while being significantly less cytotoxic to the normal counterpart (PNT2) (Figure 3).…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, BS molecules modulate immune responses by affecting the cellular and humoral arms of the immune system [ 187 , 188 , 189 ]. The immunomodulatory activity of many BSs is primarily exploited by the micro-organism to establish host infection.…”
Section: Immuno-modulatory Activity Of Bssmentioning
confidence: 99%
“…Finally, accumulating studies have demonstrated that BSs enhance immune activation and disease resistance in fish, indicating the potential application of BSs in veterinary sciences [ 188 ].…”
Section: Immuno-modulatory Activity Of Bssmentioning
confidence: 99%
“…Currently, BS are an essential component in various industrial applications (Giri et al 2020 ). BS have been investigated to strengthen marine fish defence systems against different infections and have been employed as immunostimulants in marine fish production (Giri et al 2020 ).…”
Section: Current Solutionsmentioning
confidence: 99%